Odnalezienie prawdziwego krzyża. Syryjska legenda Judy Kyriaka (Inventio verae Crucis: Syriaca legenda Judae Cyriaci) - Tronina, Antoni (Vox Patrum, 2007)
Translation of Inventio verae Crucis: Syriaca legenda Judae Cyriaci.